2017
DOI: 10.2147/copd.s120207
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of swallowing dysfunction screened in Swedish cohort of COPD patients

Abstract: BackgroundCOPD is a common problem associated with morbidity and mortality. COPD may also affect the dynamics and coordination of functions such as swallowing. A misdirected swallow may, in turn, result in the bolus entering the airway. A growing body of evidence suggests that a subgroup of people with COPD is prone to oropharyngeal dysphagia. The aim of this study was to evaluate swallowing dysfunction in patients with stable COPD and to determine the relation between signs and symptoms of swallowing dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…Additionally, tocopherols in nuts can contribute to reducing lipid degradation, which can lead to unhealthy lung conditions [37]. We also cannot rule out reverse causation, because patients suffering from chronic obstructive pulmonary disease (COPD) may have had different diets due to difficulty swallowing certain foods which could have impacted the associations we observed [38].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, tocopherols in nuts can contribute to reducing lipid degradation, which can lead to unhealthy lung conditions [37]. We also cannot rule out reverse causation, because patients suffering from chronic obstructive pulmonary disease (COPD) may have had different diets due to difficulty swallowing certain foods which could have impacted the associations we observed [38].…”
Section: Discussionmentioning
confidence: 99%
“…At the time, there was no validated dysphagia questionnaire available in Sweden. These three questions are some of the strongest clinical signs for identifying oropharyngeal dysphagia [8], they have been used in a previous study on COPD and swallowing [22] and are also used in several validated dysphagia screening protocols [21]. Thus, the patients in our study were dichotomised into either a dysphagia or nondysphagia group.…”
Section: Methodsmentioning
confidence: 99%
“…In a number of studies, the prevalence of swallowing dysfunction has been reported to be higher in patients with stable COPD than in the general population [17, 2224]. Studies on swallowing dynamics and pulmonary function have concluded that an integrated breathing and swallowing pattern is often suboptimal in patients with COPD, thereby affecting some patients' ability to swallow and to swallow safely [25].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that factors such as dyspnea associated with swallowing and lung hyperinflation may cause dysphagia. [ 15 ] Coordinated movements of muscle groups related to breath-holding, such as the diaphragm and rectus abdominis, are important to control normal apnea during swallowing. However, patients with COPD may have a hunched posture resulting in lack of coordination between the breath-holding muscles.…”
Section: Discussionmentioning
confidence: 99%